2021
DOI: 10.3390/bs11020023
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Mental Health Status among Older United States Adults with Pain

Abstract: Poor mental health is common among older adults with pain, resulting in high economic burden and impaired quality of life. This retrospective, cross-sectional database study aimed to identify characteristics associated with good mental health status among United States (US) adults aged ≥50 years with self-reported pain in the last four weeks using a weighted sample of 2017 Medical Expenditure Panel Survey data. Hierarchical multivariable logistic regression models were used to identify statistically significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Although many studies have looked at specific types of pain and psychological wellbeing, this study reports that any pain correlates with deficits in mental flexibility which may affect the psychological wellbeing of an individual. Meanwhile, a report using 2017 MEPS data looking at psychological wellbeing in older US adults with pain found that overall health status to be the greatest predictor of psychological wellbeing [ 13 ]. Physical health can have direct and indirect effects on functioning which impact psychological wellbeing such as restrictions to exercise and quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although many studies have looked at specific types of pain and psychological wellbeing, this study reports that any pain correlates with deficits in mental flexibility which may affect the psychological wellbeing of an individual. Meanwhile, a report using 2017 MEPS data looking at psychological wellbeing in older US adults with pain found that overall health status to be the greatest predictor of psychological wellbeing [ 13 ]. Physical health can have direct and indirect effects on functioning which impact psychological wellbeing such as restrictions to exercise and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Next, our study found that good overall health status was associated with lower odds of reporting poor psychological wellbeing. Good health status was also found to be the strongest predictor of good psychological wellbeing among older US adults in a further study [ 13 ]. This finding aligns with a previous mediation analysis study that found strong indirect effects between mental and physical health [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participation in economic activities may be the most influential factor in improving the quality of life of older adults. It provides a space for social participation, fulfills basic living needs, assists people in recovering from their sense of loss of a role relating to a job, and increases physical and mental satisfaction ( 29 ). Job-related activity assists older adults in recovering their health and extending their life expectancies beyond various chronic diseases they suffer from Kwak and Kim ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was interesting that perceived mental health condition was not associated with reporting a functional limitation; previous research also using MEPS data found that having any type of limitation was associated with lower likelihood of an individual reporting good mental health (AOR = 0.51, 95% CI = 0.38, 0.68) [ 33 ]. Thus, further research into the association between types of limitations and mental health status may be warranted.…”
Section: Discussionmentioning
confidence: 99%